Autoestima e sua relação com depressão, ansiedade e sofrimento psíquico em adolescentes com transtorno por uso de substâncias - Pereira, Jefferson Luiz (2019)
Substance use is a worldwide phenomenon that has a peculiar dynamic in adolescence due to the intense biopsychosocial changes and the process of identity building in that period. The development of substance use disorder (SUD) at this stage of emotional instability is strengthened by risk factors such as social vulnerability. This study is the result of a mixed method field survey with 82 adolescents in São Paulo city, of whom 33 were hospitalized for detoxification in a psychiatric hospital, constituting the case group, and 49 were students of the public network, composing the control group. The objective of this study was to verify the possible relationship between SUD, self-esteem, depression, anxiety and psychic suffering in institutionalized adolescents and, for that, the domains of self-esteem and its relationship with depression, anxiety and psychic suffering were observed and analyzed. The profile of substance use was identified by Alcohol, Smoking and Substance Involvement Screening Test (ASSIST), while self-esteem was measured by Harter's Self-Perception Profile for Adolescents. The Self-Reporting Questionnaire (SRQ-20), Beck Anxiety Inventory (BAI) and Beck Depression Inventory (BDI) were used to identify mental distress, anxiety and depression, respectively. Specific questionnaires for the case group and for the control group aimed at identifying the socioeconomic profile of participants and protection and risk factors. Results point to a negative correlation between psychological distress and global self-esteem and behavioral conduct self-esteem domain, these variables being highlighted as significant aspects within severe SUD in the studied population. Depression and anxiety, although not correlated with self-esteem, were found to be important psychic comorbidities. Family relations were presented as a protection factor compromised in this population. It is important to emphasize the contribution of psychology to the design of public policies with a view to reinforcing protection factors and coping strategies as well as reducing risk factors